Achievements and Attributions in the Context of Acquiring English as a Foreign Language: Learner Beliefs - Lázár, Viktória (Working Papers in Language Pedagogy, 2013)
Learner beliefs form an important part of individual differences within the field of language acquisition. The aim of this qualitative research is to map what beliefs adult language learners hold about achievements when learning English and what or who they attribute their success or failure to. A study applying semi-structured interviews for data collection was carried out to provide the answers. The interviews were conducted with ten experienced Hungarian adult language learners. The analysis of their answers yielded valuable insights into what learners regard as achievements in their learning process relating to the attributions necessary for successful language learning and the affective aspects of learning. The interviews also provided an overview of the respondents’ beliefs about what can compensate for the lack of aptitude, their strategy use and the effect of their age.